Re-design and making relevant university of the future through humanizing education and IR 4.0 - Salim Abeid, Amina; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2018)
Digital technologies have brought impacts to higher education, that force the universities to change their current business model. For the university to be in top ranking is a time for transformation into the new digital age and Industrial Revolution 4.0 by establishing humanizing education that creates value to the customer segments and makes the university to stay relevant in the competitive market. The aim of this paper is to seek the way on how to transform the current university into the digital capabilities, this paper uses the design thinking and system thinking approach in the transformation into the digital age and Industrial Revolution 4.0 (IR 4.0). By using business modelling tools such as Business model canvas (BMC), Value proposition canvas (VPC), Environmental map (EM) and Strategy canvas (SC) those helps in the process of analyzing, evaluating and designing business model option for the purposes of creating value to the future university. The methodology used in this paper is based on the literature review, business modelling tools, and validation from the interviews to enhance the designing of future universities business models. The sample size for the interviewers was 32 students including undergraduate, postgraduate, international, local and worked students.